2022
DOI: 10.3390/nano12030501
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Fusarium oxysporum-Based Silver Nanoparticles on Candida spp. Oral Isolates

Abstract: Candida spp. resistant to commercially available antifungals are often isolated from patients with oral candidiasis, a situation that points to the need for the development of new therapies. Thus, we evaluated the activity of Fusarium oxysporum-based silver nanoparticles (AgNPs) on Candida spp. isolated from denture stomatitis lesions. Candida isolates were molecularly identified and submitted to susceptibility assays using AgNPs and commercial fungicides. The interference on biofilm formation and the mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…AgNPs show efficient antimicrobial properties compared to other metallic NPs, due to their large surface area, which provides better contact with microorganisms. Although AgNPs have been reported to be involved in a wide range of molecular processes within microorganisms, the mechanism of action is still being studied [ 33 ], It is important to note that there are not only bacteria that cause conditions in the oral cavity, but also some yeasts such as Candida albicans [ 34 ], Recently, it has been shown that AgNPs induce alterations in fungal cells and the formation of pores on the cell surface, in addition to changes in membrane fluidity, all of which may be related to changes in the lipid constitution of the plasma membrane and membrane depolarization [ 35 ]. Regarding the mechanism of action of AgNPs on bacteria, it has been studied that they have the ability to anchor and subsequently penetrate the bacterial cell wall, which causes structural changes and cell death [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…AgNPs show efficient antimicrobial properties compared to other metallic NPs, due to their large surface area, which provides better contact with microorganisms. Although AgNPs have been reported to be involved in a wide range of molecular processes within microorganisms, the mechanism of action is still being studied [ 33 ], It is important to note that there are not only bacteria that cause conditions in the oral cavity, but also some yeasts such as Candida albicans [ 34 ], Recently, it has been shown that AgNPs induce alterations in fungal cells and the formation of pores on the cell surface, in addition to changes in membrane fluidity, all of which may be related to changes in the lipid constitution of the plasma membrane and membrane depolarization [ 35 ]. Regarding the mechanism of action of AgNPs on bacteria, it has been studied that they have the ability to anchor and subsequently penetrate the bacterial cell wall, which causes structural changes and cell death [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of these studies leads us to the following conclusions: • Fungi and plants are the main organisms that have been used for the synthesis of biogenic AgNPs to study antifungal activity. • Comparing the works in which the same species was used to synthesise AgNPs ( Marcato et al, 2012 ; Ishida et al, 2014 ; Longhi et al, 2016 ; Fonseca et al, 2022 ), we found that nanoparticles with different properties can be obtained from the same species. Therefore, it is important to consider all the above aspects about the factors that determine the antifungal activity of a biogenic AgNP, otherwise each synthesised nanoparticle must be considered as a different compound.…”
Section: Antifungal Activity Of Biogenic Agnpsmentioning
confidence: 89%
“…These nanoparticles attach to and accumulate on the fungal surface by electrostatic interaction and are actively transported inside the cell [55]. Once inside the cell, AgNP can lead to increased intracellular reactive oxygen species (ROS) [56], and alterations in multiple targets such as cell wall integrity, membrane permeability and fluidity, mitochondria metabolism, fatty acid composition, protein denaturation, and DNA damage [39,57,58]. Few studies have evaluated the antifungal effect of biogenic AgNP against C. auris.…”
Section: F4a and Indolin-3-one Display Synergistic Interactions With ...mentioning
confidence: 99%